Efficacy and safety of systemic targeted therapies for atopic dermatitis in children: A systematic review and meta-analysis - Norio Kawamoto; Hiroki Murai; Kazutaka Nogami; Takeshi Yamamoto; Tomonobu Kikkawa; Motoko Yasutomi-Sakai; Kiwako Yamamoto-Hanada; Masaki Futamura; Yukihiro Ohya (Allergology International)
Background: In recent years, several targeted therapeutic options have become available for the management of atopic dermatitis in children. In this systematic review and meta-analysis, we assessed the efficacy and safety of systemic targeted therapies for atopic dermatitis in children. Methods: A systematic review of literature available in CENTRAL, MEDLINE, Embase, and ICHUSHI databases until January 7, 2023, was performed. Randomized controlled trials of systemic targeted therapies (biologics and small molecules) on children aged 18 years or younger with atopic dermatitis were included. The primary outcomes were the eczema area and severity index (EASI) and adverse events. Other efficacy and safety outcomes were also used for meta-analysis and risk of bias analysis. Results: We included 10 studies reported in 11 articles involving three agents (dupilumab, abrocitinib, and upadacitinib) and 1760 children. Systemic targeted therapies significantly improved eczema severity with an EASI-75 response (risk ratio, 2.99; 95 % confidence interval [CI], 2.66–3.37). However, systemic targeted therapies were associated with treatment-emergent adverse events (risk difference, 0.05; 95 % CI, 0.01–0.09), particularly among small molecules in subgroup analysis, while no such trend was observed with biologics. Systemic targeted therapy also significantly improved other efficacy outcomes, and no significant association was found in the other safety outcomes. There was no risk of bias in any of the outcomes. Conclusions: Our findings indicate that systemic targeted therapies are effective and relatively safe for treating atopic dermatitis in children, although small molecules may pose a slightly higher risk of adverse events.